Muscle elasticity, strength and flexibility in high elite athlete with hamstring strain injury history - Giroux, C.; Hollville, E.; Hegyi, A.; Caumeil, B.; Morales, A.; Nordez, A.; Ruffault, A.; Edouard, P.; Couturier, A.; Rabita, G.; Guilhem, G. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Hamstring strain injury (HSI) is recognized to impair isometric strength and range of motion (ROM) during a passive straight leg raise (SLR)(1). While such deficits have been reported in various sports, little is known regarding injury-induced impairments in elite athletes. Moreover, SLR amplitude is a global measurement and does not provide information about the localized adaptations close to the injury locations. Therefore, the aim of this study is to determine the effect of HSI history on strength, flexibility and local muscle elasticity in high elite athletes.